'Where Are the Proxenoi?' Social Network Analysis, Connectivity and the Greek Poleis. Issue 1 (26th March 2022) - Mack, William
Abstract: The aim of this article is to establish a new basis for exploring the network of ancient Greek city-states during the Classical and Hellenistic periods by applying Social Network Analysis to the record of inscriptions recording grants of proxeny. Proxeny was a generalized institution for facilitating interactions between Greek political communities. Because it left a rich and idiosyncratic record in the form of thousands of honorific inscriptions, it represents an important test case for Social Network Analysis. By drawing on work on partial samples of network data, we can identify a clear and historically significant structure in this material, namely a massively unequal hierarchy in the extent to which different communities were the focus of links. This allows us to compare, systematically, the hundreds of Greek city-states in terms of their connectivity in the network. As a result it provides a new empirical basis for testing prevailing models and assumptions about why these communities forged links and mapping the limits of the network. By reading this hierarchy alongside the other information we have, we can identify the role that political, economic and geographic factors played in determining connectivity in this network, and the surprising unimportance of religion.